Labor shifting and lot sizing in garment manufacture: A simulation study - Hashemipour, M; Kayaligil, S (Univ Cincinnati Industrial Engineering, 1999)
A typical production line consisting of stages from sewing of elements through ironing of, a make-to-order garment manufacturer is studied via computer simulation. Specifically, issues of initial batches: (bundles) for later lot sizing and operator relocation among stages are addressed. Results indicate,,limited significance of-lot sizes in determining the expected delivery performance of the line due to heavily loaded assembly stage. However; results of experimentation indicate that a labor shifting policy found by a mathematical programming: model proves effective in improving the throughput rate without inducing much in-process-inventory carrying.
Keywords: garment manufacturing; lot sizing; labor shifting; simulation; throughput